Regional impact assessment: A methodology to measure the regional value added of trans-sectoral urban planning. - Carius, Nadja; Speck, Mike; Laub, Katharina (Springer, 2018)
In times of increasing interest in sustainability topics, as well as their high degree of urgency due to depletion of resources, global warming and social inequalities, concepts and respective projects that meet the goals of sustainable development experience high popularity. Additionally, phenomena like globalization and urbanization have resulted in central, environmentally deprived areas and long, interregional/international value chains with winning global players and an ever growing gap between rich and poor. Often, urban growth has outpaced the ability of governments to build essential infrastructures and create regional value. Regional value creation can be facilitated by using local trans-sectoral synergies and is fundamental to sustainable development and the strengthening of local economies. To assess the regional and sustainable impact of trans-sectoral planning in urban areas, a consistent concept is needed that not only includes economic performance indicators, but also social and ecological effects within the region. The visualization of the regional economic, environmental and social impacts cannot only support decision-making processes, but can also be used as a political argument to promote and foster trans-sectoral planning and sustainable development. There are various different approaches for measuring the regional value added, mainly focusing on the economic value added and mostly known in the field of renewable energies. To develop a tool measuring the regional impact in terms of economic, social and ecological performance of identified trans-sectoral interfaces and synergies, the authors have chosen the indicator-based approach to a value chain analysis, where a set of economic, social and ecological indicators is used for measuring the sustainability performance of value creation stages in a region. With the right choice of indicators, the tool is able to quantify the impact within a region and support the decision-making processes of urban planners.
Keywords: Regionalplanung; Stadtplanung; Nachhaltigkeit; Stadtwachstum; Infrastrukturpolitik; Wertschöpfungskette